Peritoneal dialysis technique survival at Tygerberg Hospital in Cape Town, South Africa - Kapembwa, Kenneth C; Bapoo, Nabeel A; Tannor, Elliot K; Davids, M Razeen (African Journal of Nephrology, 2017)
Background: The use of peritoneal dialysis (PD) as a treatment modality for patients with end-stage renal disease (ESRD) has been declining in many countries over the past few years. One of the reasons is technique failure, which occurs more frequently than is the case with chronic haemodialysis. Identifying and addressing the causes of technique failure is important in order to maintain more patients on PD, especially in settings where there are limited resources for chronic haemodialysis and a “PD first” approach is followed. Methods: In this retrospective study at Tygerberg Hospital in Cape Town, South Africa, we investigated 170 patients who were started on chronic ambulatory PD between January 2008 and July 2014, and determined rates of technique and patient survival. Demographic, clinical and laboratory data were assessed to identify risk factors for these outcomes. Results: The median age of the patients was 36 years and the most common cause of ESRD was glomerulonephritis. Only one patient had diabetes mellitus. Technique survival at 1, 3 and 5 years was 80%, 54% and 39%, respectively, while patient survival was 90%, 82% and 63%. Patients started on PD during the second half of the study period had improved rates of technique survival. Peritonitis was the most common cause of technique failure. Increasing age and Black ethnicity were associated with increased likelihood of technique failure. Other clinical and social factors were not significantly associated with the occurrence of technique failure. Conclusions: In our patients on PD, peritonitis, increased age and Black ethnicity were important factors associated with the development of technique failure. Concerted efforts are required to reduce peritonitis rates at our centre as this is the leading cause of technique failure.